Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
19/2
Step-by-step explanation:
3(x-6)+3=4+x
3x-18+3=4+x
2x-18+3=4
2x=19
x=19/2
[tex]3(\frac{19}{2}-6)+3=\frac{27}{2} \\4+\frac{19}{2} =\frac{27}{2}[/tex]
Answer:
x = 9.5
Step-by-step explanation:
3( x - 6 ) + 3 = 4 + x
Do the distributive property (multiply what is in the parenthesis () by 3)
3 * x + 3 * -6 + 3 = 4 + x
3x - 18 + 3 = 4 + x
Combine Like terms ( the -18 and the 3)
3x - 15 = 4 + x
Subtract x on both sides
3x - x - 15 = 4 + x - x
2x - 15 = 4
Add 15 on both sides
2x - 15 + 15 = 4 + 15
2x = 19
Divide by 2 to isolate the variable "x"
2x/2 = 19/2
x = 9.5
Check
Use substitution, now that we have the value fo "x" ( 9.5) we can substitute that into the eqaution to see if we got it correct
3( x - 6 ) + 3 = 4 + x
3( 9.5 - 6 ) + 3 = 4 + 9.5
Distribute what is in the parenthesis by 3
3 * 9.5 + 3 * -6 + 3 = 4 + 9.5
28.5 - 18 + 3 = 4 + 9.5
10.5 + 3 = 4 + 9.5
13.5 = 4 + 9.5
13.5 = 13.5
CORRECT
Hope this helped!
Have a supercalifragilisitcexpialidocious day!
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.